Estimated prevalence of congenital cardiopaties in one year-old children in Peru - Olórtegui, Adriel (2007)
The importance of congenital cardiopaties has changed in the last decades, not only due to their clinical relevance but also as it is considered a problem of public health. In our country, in spite of the advances in medical care, no studies have been done to determine the epidemilogical relevance of these deseases . Objective: To determine the epidemiologic relevance of congenital heart diseases in Peru. Design: Systematizing of epidemic studies. Setting: Department of Preventive Medicine and Public Health, Faculty of Medicine San Fernando, UNMSM. Materials: Epidemiologic studies and demographic information. Proceeding: Based on bibliographical recopilation of epidemiologic studies and demographic information, we estimated the incidence of congenital cardiopaties cases in our country for 2006-2010. Main outcome measures: Congenital cardiopaties. Results: For 2006, 3 925 cardiopaties were determined, 83,5% of them non cianotic; this prevalence would be similar annually up to 2010 and they would represent 2,5% of potentially life rate years lost per 1000 inhabitants. Conclusions: Congenital cardiopaties represent a public health problem that should be considered by the national healthcare system; also, epidemiologic studies should be undertaken.